Effect of non-invasive brain stimulation on neuropathic pain following spinal cord injury: A systematic review and meta-analysis. Issue 34 (21st August 2020) - Shen, Zhubin; Li, Zhongrun; Ke, Junran; He, Changhao; Liu, Zhiming; Zhang, Din; Zhang, Zhili; Li, Anpei; Yang, Shuang; Li, Xiaolong; Li, Ran; Zhao, Kunchi; et al.
Abstract: Background: In recent years, some studies indicated that repetitive transcranial magnetic stimulation (rTMS) could relieve neuropathic pain (NP) following a spinal cord injury (SCI), whereas some studies showed no pain relief effect. In addition, some studies showed the analgesic effect of transcranial direct current stimulation (tDCS) on NP post SCI, whereas other studies showed no effect. Methods: We systematically searched on the PubMed, Web of Science, EMBASE, Medline, Google Scholar for studies exploring the analgesic effect of rTMS or tDCS on NP post SCI until November 2019. Meta-analysis was conducted to summarize results of these studies. Results: The present quantitative meta-analysis indicated no significant difference in the effect of treatment on NP following SCI between rTMS and sham rTMS over the motor cortex at about 1 week after the end of the rTMS period (standardized mean difference (SMD) = 2.89, 95% confidence interval (CI) = −0.27 to 6.04). However, the study indicated that rTMS showed significantly better pain relief of treatment compared with sham rTMS between 2 and 6 weeks after the end of the rTMS period (SMD = 3.81, 95%CI: 0.80–7.52). However, no sufficient evidence could be provided to make a meta-analysis for the analgesic effect of tDCS on NP following SCI over the primary motor area (M1). Conclusions: In conclusion, the present meta-analysis suggested that rTMS did not show early analgesic effect on NP after SCI, but showed better middle-term analgesic effect, compared with sham rTMS. More large scale, blinded randomized controlled trials (RCTs) were needed to explore the analgesic effect of rTMS and tDCS on NP following SCI. Abstract : Supplemental Digital Content is available in the text